Pengembangan Media Belajar Audiovisual Untuk Pembelajaran Memperbaiki Motor Listrik di SMK Negeri 1 Sarolangun - Imam Khomsun (Jurnal Ilmiah Dikdaya, 2020)
Learning process for repairing electricity motor competency at skill competency of Installation Electric Power Technique at SMK Negeri 1 Sarolangun has not been run effectively. In fact, learning material in repairing electricity motor just used modul as teaching materi and media learning. While, to get the competency thad needed, learning process should be supported by leaning tool well. For answer the problem above, teacher as a fasilitator in achievment of students competency is demanded to creative in learning management. One of them is by finding alternative solution that is by develop audiovisual media for learning of repairing electricity motor that can give solution in lerning process. Development of this media aim to product efective media in learning material of repairing electricity motor at SMK Negeri 1 Sarolangun. Development model that chosen is based on Borg and Gall model that adapted lerning design Dick and Carey model. Development process is done by 5 main steps: (1) Doing analysis, (2) Design pre product, (3) Validation and revision, (4) Try out at small scale field and, (5) Try out big group field. Based on the try out of audiovisual media for learning of repairing electricity motor at the SMK, responden give suggestion that the media can be benefit in learning process at school. The reason is that media can give information about the jobs steps clearly at matery of repairing electricity motor so give ease in learning. This ease in proved by the result of try out at big group that give conclution, there is increasingly at the result of study. There by, the media can comprehand learning material fast.